Retrofitted Hydrogen-Electric Propulsion Aircraft: Performance Simulation of Critical Operating Conditions - Lammen, W.F.; Dewitte, P.A.R.; Scheers, e. (MDPI, 2025)
Retrofitting regional turboprop aircraft with hydrogen (H2)-electric powertrains, using fuel cell systems (FCSs), has gained interest in the last decade. This type of powertrain eliminates CO2, NOx, and fine particle emissions during flight, as FCSs only emit water. In this context, the “Hydrogen Aircraft Powertrain and Storage Systems” (HAPSS) project targets the development of a H2-electric propulsion system for retrofitting Dash 8-300 series aircraft. The purpose of the study described in this paper is to analyze the performance of the retrofitted H2-electric aircraft during critical operating conditions. Takeoff, as well as climb, cruise and go-around performances are addressed. The NLR in-house tool MASS (Mission, Aircraft and Systems Simulation) was used for the performance analyses. The results show that the retrofitted H2-electric aircraft has a slightly increased takeoff distance compared to the Dash 8-300 and it requires a maximum rated shaft power of 1.9 MW per propeller. A total rated FCS output power of 3.1 MW is sufficient to satisfy the takeoff requirements, at the cost of lower cruise altitude and reduced cruise speed as compared to the Dash 8-300. Furthermore, a higher-rated FCS is required to achieve the climb performance required for the typical climb profile of the Dash 8-300.